Optimization and validation of a new chromatographic method for the assay of veterinary formulation - Monir, Hany Hunter; Michael, Adel Magdy; Nessim, Christine Kamal; Fayez, Yasmin Mohamed; Elshater, Nahla Salah (European Journal of Chemistry, 2019)
New, validated and accurate reversed phase HPLC method with UV detection has been established for simultaneous determination of a veterinary binary mixture of doxycycline hydrochloride (DOX) and tylosin tartrate (TYT). The stationary phase was ACE- 126-2546 AQ C-18 (250 × 4.6 mm i.d., 5 μm particle size) column at 25 °C, in an isocratic mode, using mobile phase containing a mixture of methanol: acetonitrile: distilled water in the ratio of 60:20:20 (v:v:v), with 0.01% trichloroacetic acid at the flow rate of 0.8 mL/min and UV detection was performed at 270 nm. The retention times were 4.02±0.01 and 5.62±0.01 mins for DOX and TYT, respectively. Selective determination of the cited veterinary drugs has been developed in their formulation. The method was found to be linear over 1-50 µg/mL for DOX and TYT with mean percentage recoveries 99.62±1.220 and 100.09±1.104%. The method was proven to be accurate, precise and specific. The obtained results were statistically compared with those of the official and reported methods; using Student’s t test, F test and one-way ANOVA, showing no significant difference with high accuracy. Specificity of the applied method was assessed by analysing the laboratory-prepared mixtures and their combined dosage form. The developed method was confirmed according to ICH guidelines. The validated method can be considered as alternative and basic method for the routine determination of this fixed dose combination with minimum sample preparation.